Göçmen ağları çerçevesinde Irak Türkmen göçünün İstanbul’a yansıması - Şahin, Serdar (My University, 2013)
men Ağları, Irak Türkmenleri, İstanbul Göçmen Ağları Çerçevesinde Irak Türkmen Göçünün İstanbul’a Yansıması ÖZET Göç çalışmalarına yönelik ilgi akademik camiada her geçen gün artmaktadır. Göç ile ilgili araştırma merkezleri kurulmakta, tezler yazılmakta, eserler yayınlanmaktadır. Göç tarih boyunca bireylerin ve toplumların hayatını değiştirmeye devam etmiş bir olgu olmakta birlikte, modern dönemde kitleselleşmiş, milyonlarca kişi çeşitli sebeplerle yer değiştirmeye başlamış, 20.yüzyılda ise ‘uluslararasılaşmıştır.’ Türkiye göç hareketlerinin etkilerini çok uzun süredir hisseden bir ülke, İstanbul tarihte göçlerle yeniden kurulmuş, son yarım asırda da göç dalgalarıyla kontrolsüz şekilde büyümeye maruz kalmış bir şehirdir. Türkiye’nin insan unsurunun Osmanlı İmparatorluğu’nun son döneminde başlayan ve Cumhuriyet’in kurulmasından sonra da eden göç hareketleriyle şekillendiğini söylemek yanlış olmaz.İlk dönem göçlerin ulus devleti tahkim etmeye yönelik iken, 1950’lerden 1990’ların başına kadar devam eden göçlerin tamamına yakını iç göç özelliği göstermiş sonraki dönemde ise dış göçler artmaya başlamıştır. Özellikle komşu ülkelerden göç alan İstanbul’a göç eden gruplardan biri de Irak Türkmenleridir. Göç ve İstanbul’a tutunma süreçlerinde kurulan ‘göçmen ağları’ bu süreçleri kolaylaştırmaktadır. Büyük çoğunluğu eğitimli ve şehirli olan Türkmenler, genellikle ticaretle iştigal etmekte olup Türkiye’de yaşadıkları sorunların temelinde vatandaşlığa geçememekten kaynaklanan hukuki ve bürokratik engeller yatmaktadır. Çalışmamızın son bölümünde uygulamış olduğumuz anket ve SPSS değerlendirmesi de bu tespitleri desteklemektedir. gration, Migrant Networks, IraqiTurkmens, İstanbul The framework ofthe IraqTurkmenMigration reflections ofto İstanbulwithin MigrantNetworks.

TheInterest in theımmigrationstudies has beenincreasingconsistently in academiccommunity. New thesis’, research notes, academic books have been published and new research institutes have been established about this issue to search and solve the main problematic point of ımmigration.New thesises, research notes, academic books have been published and new research institutes have been established about this issue. Even though, The Immigration is a fact that have kept changing the people’s and society’s life through the history; In modern age, popularized millions of people have started to migrate and this fact became “Internationalization” in 20th. Century. Turkey is a county that have felt the effect of immigration for a long while. Istanbul is a city that has been reconstructed by the results of immigration in the history and in addition to this fact when we consider last half century, we can see that it is city that has been exposed to uncontrolled expansion by the effects of these immigration wawes. It will not a wrong speech that Turkey’s population structure had been formed by the immigration movement starting at the end of The Ottoman Empire’s last age and continuing after the Proclamation of Republic of Turkey.Although all of the first age’s immigrations were a movement which were realized for the nation states, strengthening almost all the immigrations between 1950’s and the beginnings of 1990’s were showing the characteristics of “internal immigration’ and as the opposite this term in the following periods external immigration has started to increase. Especially, one of the groups immigrated to Istanbul from neighboring countries was Iraqi Turkmens. “Immigrant Networks” that has been set in the period of Immigration and Adjustment to life conditions of new city Istanbul, facilitates these processes. The most part of Iraqi Turkmens population consists educated and urbanate people and they are usually dealing with commerce. Judicial and bureaucratic barriers are the main problems, because of they can’t get chance to have Turkish citizenship, that they have faced constantly. The survey and the SPSS results presented at the end of the thesis confirm these determinations as well.
Keywords: Araştırma; Göç ve Göçmenlik; İstanbul; İstanbul (Türkiye); Tarih; Türkiye